ANALISIS PEMANFAATAN DANA ZAKAT DEWAN DAKWAH ISLAMIYAH INDONESIA (DDII) PADA PROGRAM POLA KADERISASI DAI DI KABUPATEN BEKASI - Nasruloh , Diyan; Sumengkar, Apung; Yusnita , Titien (ALAMIAH : Jurnal Muamalah dan Ekonomi Syariah, 2025)
Da'wah is the responsibility of every Muslim, both male and female. The implementation of Islamic da'wah activities will be more successful if equipped with adequate expertise and skills. This research method uses a qualitative approach, which aims to investigate, find, describe, and explain the quality or specialty of social influence that cannot be measured or explained by a quantitative approach. Analysis of the Utilization of Zakat Funds in the Dai Cadre Program shows several important things. First, the need for da'wah in remote areas is very limited, while there is an increase in Christianization activities by missionaries. Second, students from these areas study religion with the hope of returning to their hometowns to da'wah. Third, the mechanism for collecting funds for financing cadre formation is carried out in two ways, namely offline and online. Fourth, the challenges faced in da'wah cadre formation include funding problems, lack of technological skills among students, and the abilities of the students themselves. Fifth, it is hoped that this cadre formation program can continue and be sustainable. Furthermore, the factors that support the success of the Analysis of Zakat Fund Utilization in the Dai Cadre Program include several aspects. First, the supervision methods applied, such as controlling, supervision from musrif, and lecturer visits. Second, steps to overcome challenges, including improving selection on campus, increasing knowledge about zakat, and preparing programs for students who experience academic difficulties. Third, the results that have been achieved include the number of Islamizations, the establishment of schools, Islamic boarding schools, and roles as marbot, muezzin, imam, and khotib, as well as teaching in pengajian. Fourth, the form of cooperation with national zakat institutions (Laznas), such as PT Paragon and the Wardah cosmetics company. Fifth, support from the government in the form of ease in licensing, and sixth, support from the community in the form of self-help funds.